Des chômeurs radiés en Belgique, entre normes et expériences vécues - Didier Demazière; Marc Zune (La Nouvelle Revue du Travail)
Qualitative sociological fieldwork on unemployed persons has ignore job searching. Yet this is a key component of activation policies that aim to transform unemployed persons into job seekers. The article analyses the tensions between these activation norms and individuals’ personal experiences, based on the rarely studied situation where unemployed benefits recipients are taken off the dole because they are not deemed to be looking for a job. In-depth interviews with these de-registered unemployed persons make it possible to understand how they engage in job searching and the meaning they attach to this act. The demonstration here is that their job search experiences are not considered legitimate because they deviate from an institutional framework requiring tangible evidence attesting to job searches. Unemployed persons taken off the dole are in fact often looking for a job. The problem is that they are pursuing an alternative approach that is less formal or explicit than the processes recognised and validated by public sector job centres.